Polemically around Rousseau. Defensive Remarks to the Critical Remarks of Michał Kruszelnicki - Pieniążek, Paweł (Hybris, 2024)
The text is a polemic against the polemical-critical remarks by Michał Kruszelnicki to my book entitled Individual, evil, history in Rousseau’s thought (Łódź 2022). It deals with key issues and problems in Rousseau’s thought that have long plagued the minds of commentators on his work. In my discussion with the Polemist, I maintain the main theses and interpretative solutions presented in the book, starting from a different view of Rousseau’s work, that is, emphasising its evolution and rejecting the Polemist’s conciliatory-humanist, though not always consistent, interpretation, which generally attempts to reconcile most of the strands of Rousseau’s thought. Nevertheless, his legitimate, interesting and unconventional and sometimes, I think, somewhat provocative remarks have forced me to renew my conceptual and interpretative efforts and, as a result, to develop and deepen the arguments and analyses in the book, which are not always clear and may give rise to misunderstanding. Thus, in particular, I develop my understanding of the relationship between experimental logic and systemic logic, showing their common complementary dynamics, defend the thesis of the failure of Rousseau’s work attempting to synthesise the communitarian and individualist perspectives of his thought to show the abandonment of these attempts in the solitary-contemplative Strolls of a Lonely Dreamer, and, finally, highlight argumentatively the authoritarian implications of Rousseau’s political and pedagogical ideas.